If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 = 26 + 4x Reorder the terms: -2 + 3x = 26 + 4x Solving -2 + 3x = 26 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -2 + 3x + -4x = 26 + 4x + -4x Combine like terms: 3x + -4x = -1x -2 + -1x = 26 + 4x + -4x Combine like terms: 4x + -4x = 0 -2 + -1x = 26 + 0 -2 + -1x = 26 Add '2' to each side of the equation. -2 + 2 + -1x = 26 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 26 + 2 -1x = 26 + 2 Combine like terms: 26 + 2 = 28 -1x = 28 Divide each side by '-1'. x = -28 Simplifying x = -28
| 7r=-10+5r | | 2a-1+7= | | 5x(x-5)/2= | | -2t=-8-4t | | 10y^2+11y-6=5 | | 2y=16x+39 | | Y-11.5=6/5(x-7) | | -5u+10=4u-8 | | x^2-12-10=-8x+2 | | (4x+3)(3X+2)=0 | | -6m=3m-9 | | 8q+10=7q | | 4p+6=2p | | 18x+24y=3680 | | 5X-2X=700-400 | | 5x-20=3x-10 | | y=1100-7x | | 0.02X^2-50x-5y-5000=0 | | (x-6)2=0 | | 8(3x+5)=4 | | 9x-24= | | x-7/2:x=-20/7 | | 2A+3+2(A-3)=4 | | 5N-3(N-2)=N+3 | | (3/4(x^2))-(3/2x)-(1/4)=0 | | 3(M-2)-2M=5 | | 2k(k+7)=2k^2+2(7)k | | 0.10x+0.05y=5.75 | | 5x+20=3x-20 | | 29x-50=22-2x | | 5x-9=82-8x | | 2(x-1)=3x-8 |